Unconventional sisterhood : feminist Catholic nuns in the Philippines - Claussen, Heather L., 1968- (Southeast Asia--politics, meaning, memory., 2001)
"Unconventional Sisterhood is an ethnographic exploration of the ways in which Filipina Missionary Benedictine Sisters are renegotiating traditional understandings of gender, religious responsibility, and national identity in the context of a rapidly globalizing nation. And, unlike the popular stereotypes of staid sisters cloaked in rigid religious dogmatism, they are doing so by telling jokes, engaging in eclectic religious rituals, maintaining connections with a local nationalist cult, and committing themselves to a radical - and feminist - politics."--Jacket